2014
DOI: 10.1177/1557988314531446
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Scar Origin in Shaping Men’s Body Image

Abstract: Men generally have a more positive body image than women. However, the extent to which scars negatively influence men’s body image is uncertain. The aim of the current study was to assess body image in men with and without scars while taking scar origin into account (nonsuicidal self-harming injuries [NSSI] vs. accidents or surgery). One hundred and nine men ( n = 19 with NSSI) and 185 women ( n = 96 with NSSI) filled in multidimensional body image questionnaires. Results indicate that on most clinical subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Dyer and colleagues (2013) found that among females, those with NSSI scarring exhibited a significantly more negative body image than those with scars of alternate origins, even after controlling for scar characteristics (e.g., size, appearance), borderline personality symptoms, and body mass index. These results have been replicated among men (Dyer et al 2015). More recently, Burke and colleagues (2016) found that the presence and number of NSSI scars were significantly associated with current suicidal ideation, after controlling for depressive symptoms, suicide attempt history, NSSI method, NSSI medical severity, and NSSI frequency.…”
mentioning
confidence: 60%
“…Dyer and colleagues (2013) found that among females, those with NSSI scarring exhibited a significantly more negative body image than those with scars of alternate origins, even after controlling for scar characteristics (e.g., size, appearance), borderline personality symptoms, and body mass index. These results have been replicated among men (Dyer et al 2015). More recently, Burke and colleagues (2016) found that the presence and number of NSSI scars were significantly associated with current suicidal ideation, after controlling for depressive symptoms, suicide attempt history, NSSI method, NSSI medical severity, and NSSI frequency.…”
mentioning
confidence: 60%
“…Furthermore, only two empirical studies have directly examined the psychological effects of scarring from NSSI (Dyer et al, 2012; Dyer et al, 2014). Specifically, Dyer and colleagues (2012, 2014) found, and then replicated their findings, that among females and males, recruited specifically for scarring, those with NSSI scarring endorsed a significantly more negative body image in general and after scarring than those with scars of alternate origins, even after controlling for scar size and appearance. These studies provide important preliminary evidence that the presence of NSSI scarring might be psychologically damaging.…”
Section: Introductionmentioning
confidence: 99%
“…Burke and colleagues (2017) found that those who reported greater negative socially-related cognitions (e.g., shame, embarrassment) about their scars exhibited higher levels of social anxiety, depression, and suicidal ideation. Other literature has found that NSSI scars are associated with significantly elevated levels of negative body image, including lower appearance evaluation and body area satisfaction (Dyer, Hennrich, Borgmann, White, & Alpers, 2013; Dyer, Mayer-Eckhard, White, & Alpers, 2015). Taken together, this literature suggests that permanent scarring from NSSI may have a detrimental impact on individuals’ psychological health.…”
mentioning
confidence: 99%